Cloud and virtual data storage networking : your journey to efficient and effective information services - Schulz, Greg (CRC Press, 2012)
Schulz provides comprehensive coverage of IT data storage networking infrastructure, including public and private cloud, virtualization, and traditional IT environments. He examines strategies for the design, implementation, and management of hardware, software, and services technologies.